A new approach for the identification of strategic Italian ports for container traffic. (May 2022) - Carrese, Stefano; Petrelli, Marco; Renna, Alessandra
Abstract: This study proposes a methodology able to identify strategic ports based on port system situation and different evolution scenarios. In particular, the present paper adopts the analytic hierarchy process as tool for the port selection process in combination with the scenario planning method for measuring and explicitely considering the uncertainty for the future evolution of the port system. The proposed methodology is structured in three main phases. The first phase consists in the database construction for selecting the ports to rank and identifying all the ports characteristics to be used in the selection process. The second phase is the scenario building to identify the possible evolution of the Italian port system in the sector of container traffic. Finally, the third phase is the applications of the analytic hierarchy process for each scenario developed in the previous phase. The key factors have been settled to provide seven criteria and the applications carried out for any scenario are different only in the scores assigned to the criteria according to the different importance assigned to endogenous and exogenous factors. The numerical application of the selection process developed is carried out for the Italian port system after a comparison analysis of situation between before and during Covid-19 pandemia. The application shows that the ports of the Northern Italy are always in the first positions (Trieste, Genoa, La Spezia and Livorno) while the ports of the Southern Italy highlight some limits. The strength and the robustness of the defined process, also in considering uncertainty, are proven by the ranking occupied by Genoa and Trieste, always in the first positions, that in the last years seem more dynamic and interesting than other ports so attracting many investments from private operators. Highlights: AHP application for port selection process in combination with scenario planning technique Numerical application carried out for the Italian port system for container traffic Analysis of the Italian ports system before and during the Covid-19 pandemic period Seven criteria settled for selection based on endogenous and exogenous port factors